DAMPAK KEBIJAKAN ANTI-RESETTLEMENT AUSTRALIA TERHADAP PENGUNGSI ASING ASAL AFGHANISTAN DI PEKANBARU - Marpaung, A. Rivalno Marpaung; Jamaan, Ahmad (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
The purpose of this research is to determine the condition of foreign refugees from Afghanistan in Indonesia as well as the history of the early background of refugees coming to Indonesia. Also to find out the cause of Australia cutting off the resesttelement of refugees in Indonesia. How the impact of the anti-resettlement policy on foreign refugees from Afghanistan in Pekanbaru and the attitude of refugees after the Anti-Resettlement policy in Pekanbaru. This study was analyzed using qualitative methods with interview techniques of foreign refugees from Afghanistan, observation and literature. Using migration theory according to Khalid Koser in 2003 stated in his book entitled